2019
DOI: 10.1186/s13075-018-1796-4
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial activation and injury by microparticles in patients with systemic lupus erythematosus and rheumatoid arthritis

Abstract: Background Endothelial activation and damage is commonly observed in patients with systemic lupus erythematosus (SLE) and rheumatoid arthritis (RA) and is related to development of atherosclerosis and cardiovascular diseases. Different components of the immune system seem to participate in the endothelial injury, such as generation of autoantibodies and formation of immune complexes (ICs). Microparticles (MPs) and their immune complexes (MPs-ICs) are increased in the circulation of patients with S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 61 publications
0
40
0
1
Order By: Relevance
“…Several reports suggest receptor-mediated and redox signalling mechanisms lead to endothelial dysfunction. [20][21][22][23][24][25][26] Our laboratory has published that eNOS is uncoupled with addition of lupus serum. 17 This uncoupling leads to production of reactive oxygen species in an animal model of LN and in LN glomerular tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports suggest receptor-mediated and redox signalling mechanisms lead to endothelial dysfunction. [20][21][22][23][24][25][26] Our laboratory has published that eNOS is uncoupled with addition of lupus serum. 17 This uncoupling leads to production of reactive oxygen species in an animal model of LN and in LN glomerular tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was shown that these increased EVs in the plasma of active SLE patients induced ROS production and degranulation in neutrophils 187 , activated pDCs to secrete IFN-α via TLR7 188 , or contributed to MSC senescence in SLE 189 . The elevated EVs and their immune complexes in SLE patients also promoted secondary leukocyte infiltration by regulating vascular remodeling and chemokine secretion 16 . Moreover, EVs derived from platelets mostly harbored IgG and overexpressed CD69 and CD64, and promoted pro-inflammatory responses in monocytes, thus exacerbating SLE-associated inflammation 190 .…”
Section: Ev Involvement In the Pathophysiology Of Inflammatory Skin Dmentioning
confidence: 99%
“…Recent work from us and others has indicated that EVs play key immunomodulatory roles in the pathogenesis of various inflammatory skin diseases, such as psoriasis 11 , 12 , atopic dermatitis (AD) 13 , lichen planus (LP) 14 , bullous pemphigoid (BP) 15 , systemic lupus erythematosus (SLE) 16 , and chronic wound healing 7 . These inflammatory skin disorders pose major problems in dermatology given their complex pathophysiology and refractory nature, which ultimately pose a burden to the health, economic and social systems.…”
Section: Introductionmentioning
confidence: 99%
“…Platelet-derived microparticles generate thrombin, thereby aggravating hypercoagulability. Circulating microparticles, including those derived from endothelial cells, are novel biomarkers in SLE [ 17 ], but studies have not related these to clinical disease activity [ 3 , 18 , 19 , 20 ] or evaluated for cardiovascular risk in SLE the proportion of IgG-decorated microparticles that also fixed complement [ 21 ].…”
Section: Gap In Knowledgementioning
confidence: 99%